(untitled) (Revista Direito em Debate, 2024)
This research aims to analyze whether the current legislation addresses the use of drones intended for use in public security, and whether this indiscriminate use can harm the privacy and intimacy of citizens as fundamental personality rights. Thus, the aim is to uncover the use of this tool in the hands of state power, investigating existing regulations and evaluating the impact of these technologies on individual rights. We sought to demonstrate that private life is threatened by the use of this technology in the day-to-day activities of the police in their crime prevention activities in the name of a “greater good”, which is the community. For this to be successful, the hypothetical-deductive methodology was used through the theoretical-bibliographic method, with data collection carried out on academic search sites, libraries, current legislation and scientific journals that address the topic. The results obtained circulate in the violation of personality rights in the face of privacy and intimacy, which is outraged by the indiscriminate use of far-reaching technologies and difficult to limit a surveillance filter, in which in the name of the community the sphere is harmed. most individual aspect of human life.